An Anthrax Lethal Factor-Neutralizing Monoclonal Antibody Protects Rats before and after Challenge with Anthrax Toxin - Lim, Nam-Kyu (American Society for Microbiology, 2005)
Lethal factor (LF) is a component of anthrax lethal toxin (LeTx). We generated anti-LF murine monoclonal antibodies (MAbs) that show LeTx-neutralizing activity in vitro and in vivo. Anti-LF MAbs were generated by immunization with recombinant LF, and the MAbs showing LeTx-neutralizing activity in vitro were selected. Two MAbs with the highest affinities, 5B13B1 (dissociation constant [K(d)], 2.62 nM) and 3C16C3 (K(d), 8.18 nM), were shown to recognize the same or closely overlapping epitopes on domain III of LF. The 50% inhibitory concentration of 5B13B1 (0.21 μg/ml) was approximately one-third that of 3C16C3 (0.63 μg/ml) in the in vitro LeTx-neutralization assay. The 5B13B1 antibody, which had the highest neutralizing activity, provided perfect protection against LeTx challenge in an in vivo LeTx neutralization assay using Fisher 344 rats. In addition, the antibody showed pre- and postexposure prophylactic effects in the animal experiments. This is the first report that an MAb binding to domain III of LF has neutralizing activity against LeTx. The 5B13B1 antibody may be useful in prophylaxis against anthrax poisoning.